2017
DOI: 10.1038/ni.3772
|View full text |Cite
|
Sign up to set email alerts
|

Limiting inflammation—the negative regulation of NF-κB and the NLRP3 inflammasome

Abstract: A properly mounted immune response is indispensable for recognizing and eliminating danger arising from foreign invaders and tissue trauma. However, the 'inflammatory fire' kindled by the host response must be tightly controlled to prevent it from spreading and causing irreparable damage. Accordingly, acute inflammation is self-limiting and is normally attenuated after elimination of noxious stimuli, restoration of homeostasis and initiation of tissue repair. However, unresolved inflammation may lead to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
428
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(442 citation statements)
references
References 114 publications
12
428
0
2
Order By: Relevance
“…In the context of NF-κB regulation, one of the best characterized RBPs is Tristetraprolin (TTP). TTP is considered a prototypic member of the RBPs and regulates NF-κB signaling by facilitating mRNA degradation [3, 118]. Specifically, TTP binds to mRNAs rich in AU-rich elements (AREs), which includes TNF and IL-23, and induces degradation [119].…”
Section: Post-transcriptional Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of NF-κB regulation, one of the best characterized RBPs is Tristetraprolin (TTP). TTP is considered a prototypic member of the RBPs and regulates NF-κB signaling by facilitating mRNA degradation [3, 118]. Specifically, TTP binds to mRNAs rich in AU-rich elements (AREs), which includes TNF and IL-23, and induces degradation [119].…”
Section: Post-transcriptional Inhibitionmentioning
confidence: 99%
“…This process is typically reversible, allowing a high level of temporal or tunable control, and usually occurs on serine, threonine, or tyrosine residues. In the NF-κB signaling pathway, phosphorylation can induce conformational changes in proteins such as IRAK and the IKK kinases, resulting in the release of auto-inhibition and increased enzymatic activity [3]. Conformation changes associated with phosphorylation can also promote or facilitate protein-protein interactions, such as those associated with IκBα or caspase-recruitment-domain (CARD) proteins [3].…”
Section: Post-translational Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to control such potential harmful effect of inflammation, inflammatory pathways and their activators are tightly controlled by a network of regulators and feedback loops (3).…”
mentioning
confidence: 99%
“…Cytokines in turn not only promote MM cell growth, but also increase resistance to conventional therapies [12, 13]. In recent years, more and more studies have shown that an inflammasome in tumor microenvironments can trigger carcinogenesis, and has significant impacts on tumor immunity and immunotherapy, thus providing new insight into the effective therapies [14, 15]. The most studied inflammasome is the NLRP3 inflammasome, and mounting evidences support that the NLRP3 inflammasome plays an important role in the development of malignant tumors [16, 17].…”
Section: Discussionmentioning
confidence: 99%